Arbitration in India - Dave, Dushyant; Hunter, Martin; Nariman, Fali S.; Paulsson, Marike (Kluwer Law International B.V., 2021)
India has a long-standing tradition of dispute resolution through arbitration, with arbitral-type regulations going back to the eighteenth century. Today, amendments to the 1996 Indian Arbitration Act, a steady evolution of case law and new arbitral institutions position India's vibrant system once more at the forefront of international commercial dispute resolution. In this handbook, over forty members of the international arbitration community in India and beyond offer authoritative perspectives and insights into topics on arbitration that matter in India. International arbitration practitioners, Indian practitioners, and scholars have combined efforts to produce a practical and informative guide on the subject. Among numerous notable features, the contributors provide detailed analysis and description of such aspects of arbitration as the following, with a focus on the Indian context: Indian application of the 1958 New York Convention; law governing the merits of the dispute and awards; investor-state dispute settlement; drafting arbitration clauses for India-centric agreements; managing costs and time; rise of virtual arbitration and technology; effect of public policy in light of extensive Indian jurisprudence; and arbitration of claims relating to environmental damage. Practical features include checklists for drafting arbitration clauses and a comparative chart of major commercial arbitration rules applicable to India. Also included is a comparative analysis of arbitral regimes in India, Singapore and England; chapters on the India Model Bilateral Investment Treaty and ISDS reforms; a special section on the enforcement of foreign awards; a section on the drafting of the award guided by leading arbitrators and stakeholders and a review of the new 2021 ICC Rules.